Internal digitalization and tax-efficient decision making - Daniel Klein; Christopher A. Ludwig; Katharina Nicolay (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
Our study investigates firms' internal digitalizationas a crucial foundation for timely, data-driven decision making. We evaluate the association between digital infrastructure and improved decision making intax planning decisions to analyze if the benefits of digitalization expand beyond firms' core business functions. The novel use of a survey that identifies European firms' digital infrastructure over the period from 2005 to 2016 allows us to create an index of IT sophistication. Using this index, we extend prior approaches and observe the effectiveness of tax planning decisions in terms of a firm's ability to exploit income shifting incentives. Our empirical analysis confirms the prediction that digitalized firms respond more efficiently to income shifting incentives. Further, we provide evidence that firms with sophisticated IT are more reactive to shocks in the income shifting incentive than non-digital firms. Our results suggest that internal digitalization allows firms to efficiently monitor and manage internal processes and to strategically price internal transactions. With this work, we are the first to document the association of digitalization and the performance of firms' support functions.
Keywords: O33; L25; H25; H26; K34; 330; Digital Transformation; Digitalization; Firm Performance; Decision Making; Multinational Corporations; Business Taxation; Information Technology; Profit Shifting